Face Mask Wearing Behaviors, Depressive Symptoms, and Health Beliefs Among Older People During the COVID-19 Pandemic - Kwan, Rick Yiu Cho; Lee, Paul Hong; Cheung, Daphne Sze Ki; Lam, Simon Ching (Frontiers in Medicine, 2021)
The COVID-19 pandemic has affected more than 100 countries. Despite the global shortage of facemasks, the public has adopted universal mask-wearing as a preventive measure in many Asian countries. The COVID-19 mortality rate is higher among older people, who may find that wearing a facemask protects their physical health but jeopardizes their mental health. This study aimed to explore the associations between depressive symptoms, health beliefs, and facemask wearing behaviors among older people. By means of an online survey (March-April 2020), we assessed these variables among community-dwelling older people. General linear models were employed to explore the associations among these variables. Of the 355 participants, 25.6% were depressive. Health beliefs regarding the perceived severity of disease (p=0.001) and perceived efficacy of practicing preventive measures (p=0.005) were positively associated with facemask use. Those who reused facemasks (p=0.008), had a better perceived severity of disease (p<0.001), and had a poorer cue to action (p=0.002) were more likely to experience depressive symptoms. Mask reuse was significantly associated with depression only among those who perceived the disease as serious (p=0.025) and those who had poorer cues to preventive measures (p=0.004). In conclusion, health beliefs regarding perceived severity and efficacy contributed to better facemask use, which was unrelated to depressive symptoms. Older people with health beliefs regarding perceived severity, those with poorer cues to prevention measures, and those who reuse facemasks were more depressive. A moderation effect of health beliefs (i.e., disease severity and cues to preventive measures) on facemask reuse and depression was observed.